Genetic study of Salmonella spp. Producting Betalatimase (ESBLs) - Baghdad Science Journal (مجلة بغداد للعلوم)
Ten isolates were collected from different clinical sources from laboratory in medicine century . These isolates were belonging to the genus Salmonella depending on morphological and biochemical tests . The antibiotic scussptibility tests against 10 antibiotics were examined , and it was found that the 60% isolates have multiple resistant to antibiotic ,(70%) of isolates were resistant to ampicillin,(50%) were resistant to augmentin ,(40%) were resistant to ceftriaxone ,(20%) were resistant to cefotaxime and (10%) were resistant to ciprofloxacin and tetracycline while all isolates showed sensitivity to piperacillin, imipenem, amikacin and erythromycin .The ability of Salmonela isolates to produce ?-lactamase enzymes were tested using iodometric method , and the results showed that all isolates produced this enzyme.The ability of these isolates to produce Extended-Spectrum ?-lactamase (ESBLs)were also determined by double disc synergy test , only five isolates produced these enzyme. Agarose gel electrophoresis showed that Salmonella isolates ?-lactamase producer have two small plasmid bands . Transformation experiments revealed that these plasmids were capable to transform E. coli MM294, an observation which indicates the ability of these plasmids to show their expression in more than one host.